Ekstrak Daun Cocor Bebek (Kalanchoe pinnata) untuk Terapi Preventif Lupus pada Mencit yang Diinduksi dengan 2,6,10,14 Tetramethylpentadecane (Journal of Tropical Pharmacy and Chemistry, 2025)
Cocor bebek Plants (Kalanchoe pinnata) has been observed to have a potent immunosuppressant compounds in BALB/c mice with Delayed Type Hypersensitivity test (DTH). Compounds are efficacious immunosuppression can be used for treatment of autoimmune diseases such as lupus. The purpose of this study was knowing the class of compounds in leaf extracts cocor bebek and test whether the extract can prevent the occurrence of lupus in test animals. Methods: In this study the identification of classes of compounds present in Cocor bebek leaf extracts and testing imunnosupression activities from test animals BALB/c mice induced lupus using 2,6,10,14 tetramethylpentadecane (TMPD). Parameters measured lupus glomerulonephritis which was known by the presence of proteinuria using a test strip supported by data on changes in weight. Results: Extracts of cocor bebek leaves positive contain tannins, flavonoids, saponins and steroid / triterpene. Mice given the extract of Cocor bebek leaves every day until the 3rd month after not having induced proteinuria, while untreated mice had proteinuria up to +2 (proteinuria levels> 30 mg / dL).